Assessing Changes in Ecological Quality Status of Sediment in Tri An Reservoir (Southeast Vietnam) by using Indicator of Nematode Communities - Thai, Tran Thanh; Luu, Pham Thanh; Hoang Yen, Tran Thi; My Yen, Nguyen Thi; Quang, Ngo Xuan (VNU Journal of Science: Natural Sciences and Technology, 2020)
Nematode communities in Tri An Reservoir (Dong Nai Province, Southeast Vietnam) were explored in the dry season (March) and pre-rainy season (July) of 2019 and analyzed to evaluate their usage as bioindicators for ecological quality status of sediment. Nematode communities consisted of 23 genera belonging to 19 families, 8 orders for the dry and 24 genera, 17 families, 8 orders for the pre-rainy season. Several genera dominated in Tri An Reservoir such as Daptonema, Rhabdolaimus, Udonchus, and Neotobrilus indicated for organic enrichment conditions. The percentage of cp3&4 and MI (Maturity Index) value in the dry season was higher than that in the pre-rainy season expressed the ecological quality status of sediment in the dry season were better than those in the pre-rainy season. Furthermore, the result revealed that MI and c-p% composition can be used to evaluate the ecological quality status of sediment efficiently. Keywords : Bioindicator, ecological quality status of sediment, freshwater habitats, maturity index, nematodes, reservoir.